1993
DOI: 10.1038/362255a0
|View full text |Cite
|
Sign up to set email alerts
|

Germ-line transmission and expression of a human-derived yeast artificial chromosome

Abstract: Introduction of DNA fragments, hundreds of kilobases in size, into mouse embryonic stem (ES) cells would greatly advance the ability to manipulate the mouse genome. Mice generated from such modified cells would permit investigation of the function and expression of very large or crudely mapped genes. Large DNA molecules cloned into yeast artificial chromosomes (YACs) are stable and genetically manipulable within yeast, suggesting yeast-cell fusion as an ideal method for transferring large DNA segments into mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(44 citation statements)
references
References 19 publications
0
42
0
2
Order By: Relevance
“…Position-independent expression has rarely been achieved with conventional transgenes (35). However, among the four recent reports of transgenic mice carrying YAC (21)(22)(23)(24), two (21,22) have shown position-independent transgene expression, and three (21)(22)(23) Although the levels of mouse and human APP770 transcripts were comparable in the three ES cell lines the level of human APP751 transcript was slightly higher than the level of mouse APP751 transcript. This difference may reflect either a bias for processing of the primary human APP transcript toward the APP751 splice product or a difference in stability between mouse and human APP751 mRNAs.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Position-independent expression has rarely been achieved with conventional transgenes (35). However, among the four recent reports of transgenic mice carrying YAC (21)(22)(23)(24), two (21,22) have shown position-independent transgene expression, and three (21)(22)(23) Although the levels of mouse and human APP770 transcripts were comparable in the three ES cell lines the level of human APP751 transcript was slightly higher than the level of mouse APP751 transcript. This difference may reflect either a bias for processing of the primary human APP transcript toward the APP751 splice product or a difference in stability between mouse and human APP751 mRNAs.…”
Section: Methodsmentioning
confidence: 92%
“…Recently, methods for the introduction of yeast artificial chromosomes (YACs) into mice have been developed (21)(22)(23)(24). Because genomic-DNA-based transgenes permit expression of alternatively spliced transcripts and are more likely to be appropriately regulated than cDNA transgenes (25), we have introduced a 650-kb YAC containing the entire human APP gene into embryonic stem (ES) cells by the colipofection procedure (24).…”
mentioning
confidence: 99%
“…Several studies have demonstrated efficient transgene expression through the transfer of YAC DNA into ES cells, suggesting that YACs can act as independent transcriptional units (21,36,54,61,65). Of particular relevance have been transgenic studies using YACs containing the human ␤-globin locus to examine the role of the LCR in controlling globin gene switching.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative approach, one may consider unbiased or "top-down" strategies to cis element dissection in which large genomic fragments are utilized at the outset in an effort to recapitulate correct developmental and quantitative gene expression. Such approaches are based on the demonstration that the stable transfer of yeast artificial chromosomes (YACs) containing large contiguous genomic DNA fragments into mammalian cells leads to proper transgene expression (36,61,65). In principle, the combined use of manipulation of YACs in yeast and transfer of YACs into embryonic stem (ES) cells provides a powerful strategy with which to investigate and identify novel distant regulatory domains within a gene locus.…”
mentioning
confidence: 99%
“…We set out to determine whether we could recapitulate the transcriptional state of the maternal chromosome using a yeast artificial chromosome (YAC) that contains the two genes as well as the tightly linked Ins2 gene. YACs have proven useful in the analysis of large gene complexes in mammals, as they can be readily modified in yeast and then transferred into either tissue culture cells or mice (26,27,37,46,52). As Saccharomyces cerevisiae lacks the CpG methylation found in mammals, the YACs were expected to mimic the hypomethylated state of the maternal chromosome.…”
mentioning
confidence: 99%